PENGARUH KUALITAS AUDIT, FINANCIAL STABILITY, DAN KARAKTERISTIK KOMITE AUDIT TERHADAP FINANCIAL STATEMENT FRAUD PADA PERUSAHAAN YANG TERGABUNG DALAM INDEKS LQ 45 - Suripto Suripto; Jayadih Jayadih (ITB AAS INDONESIA, 2022)
This research aims to prove empirically the influence of audit quality, financial stability, and audit committee characteristics against financial statement fraud. This research was conducted in companies that are members of the LQ-45 Index listed on the Indonesia Stock Exchange for 2016-2020. The research method used is descriptive of associative. The type of data used is secondary data. Samples are collected using the purposive sampling method. The number of companies used as a sample of research as many as 21 companies with a research period of 5 (five) years, so that as many as 105 observation data were obtained. Processing data using the Microsoft Office Excel Program and the Eviews Statistics 9 Program. Statistical test results F variables of audit quality, financial stability, and audit committee characteristics influence simultaneously on financial statement fraud. The results of the financial stability variable test and the characteristics of the audit committee partially have a positive and significant effect on financial statement fraud. However, the audit quality variables partially have no effect on financial statement fraud.